2017
DOI: 10.5897/ajmr2017.8716
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum beta-lactamase- and carbapenemase-producing Enterobacteriaceae clinical isolates in a Senegalese teaching hospital: A cross sectional study

Abstract: Extended spectrum β-lactamase (ESBL) and carbapenemase-producing Enterobacteriaceae (CPE) have been increasingly reported worldwide. The objective of this study is to determine the prevalence of these multidrug-resistant strains in a major university teaching hospital in Dakar, Senegal. A total of 1205 Enterobacteriaceae stains were tested for ESBL and carbapenemase production. Antibiotics susceptibility test was performed with disk diffusion method. ESBL was detected using a double-disk synergy method. Carbap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
3
8
2
Order By: Relevance
“…High resistance was detected to cefotaxime, cefoxitin also (79.6% and 81.6% among ESBL producers respectively and 36.7% and 33.3% among carbapenemase producers; respectively). A study in Senegal showed that all strains were resistant to ceftriaxone or cefotaxime (99.9%) [27]. In the present study low rates of resistance to amikacin was detected, which is consistent with findings from Korea [45], Taiwan [31], Japan [46] and Senegal [27].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…High resistance was detected to cefotaxime, cefoxitin also (79.6% and 81.6% among ESBL producers respectively and 36.7% and 33.3% among carbapenemase producers; respectively). A study in Senegal showed that all strains were resistant to ceftriaxone or cefotaxime (99.9%) [27]. In the present study low rates of resistance to amikacin was detected, which is consistent with findings from Korea [45], Taiwan [31], Japan [46] and Senegal [27].…”
Section: Discussionsupporting
confidence: 91%
“…A study in Senegal showed that all strains were resistant to ceftriaxone or cefotaxime (99.9%) [27]. In the present study low rates of resistance to amikacin was detected, which is consistent with findings from Korea [45], Taiwan [31], Japan [46] and Senegal [27].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations